The Influence of Brand Awareness and Word of Mouth on the Decision to Use the FLIP Application (Case Study of Young Mothers in the dBestMom Community) - Yuda, Aditya Pratama; Vetalidya, Vetalidya (Asian Journal of Applied Business and Management, 2024)
This research aims to determine the influence of word of mouth on the decisions of users of PT Flip Lentera Inspirasi Pertiwi, to determine the influence of brand awareness on the decisions of users of PT Flip Lentera Inspirasi Pertiwi and to determine the influence of word of mouth and brand awareness simultaneously on the decisions of PT Flip Lentera Inspirasi users. Mother Earth. The sampling technique used the Slovin formula. The population in this study was 178 consumers. The sample used was 64 respondents using questionnaire data collection techniques. The nature of the research used is quantitative associative. Data analysis methods used include validity tests, reliability tests, classical assumption tests, simple linear regression tests, multiple regression equations, correlation coefficient tests, coefficient of determination tests, and hypothesis tests. Based on the research results, word of mouth has a significant effect on user decisions, which can be seen from the results of the tcount test = 2.860, while ttable = 1.998 (tcount > ttable) with a significance level of 0.003 < 0.05, brand awareness has a significant effect on user decisions, which can be seen from the results of the tcount test. = 4.607 while ttable = 1.998 (tcount > ttable) with a significance level of 0.006 < 0.05.